2020
DOI: 10.1177/1934578x20951417
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Effect of the Iridoid Glycoside Fraction from Dipsacus fullonum L. Leaves

Abstract: Species of Dipsacus have been widely used in folk medicine for their neuroprotective, antiosteoporotic, antioxidative, anticomplementary, and antibacterial activities. However, there has been but a limited amount of research on the anticancer effect of one of the most popular representatives of this genus, D. fullonum. Also, the cytotoxic activity has not yet been investigated of the constituents of D. fullonum leaves. The purpose of this study was to evaluate the cytotoxic activity of the bis-iridoid glycosid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
1
10
0
1
Order By: Relevance
“…Based on the WST-1 assay results, the cytotoxicity arose from polyphenols as the NP7 fraction had a viability of 54.7 ± 9.2%. These results correlate with those of our previous studies on iridoid fractions having a 63.3 ± 13.7% viability [18]. The detailed results of the statistical comparison test are given in Supplementary Materials File S1.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Based on the WST-1 assay results, the cytotoxicity arose from polyphenols as the NP7 fraction had a viability of 54.7 ± 9.2%. These results correlate with those of our previous studies on iridoid fractions having a 63.3 ± 13.7% viability [18]. The detailed results of the statistical comparison test are given in Supplementary Materials File S1.…”
Section: Resultssupporting
confidence: 88%
“…A similar fraction produced and tested previously by our group has shown activity against the selective cytotoxic effect on human breast cancer cell lines MCF7 and MDB-MD-231 [18]. Fraction NP5 contained mainly loganic acid, which also exhibited anti-Borrelia activity, similarly to iridoids from fraction NP2.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…Studies of medicinal plants have demonstrated that the health-promoting properties and therapeutically beneficial qualities can often be attributed to specific polyphenols or iridoids, two of the most prevalent groups of bioactives in many plant extracts, and in the representatives of the Galium genus [ 9 , 11 , 16 , 17 ]. Polyphenols are the most abundant secondary metabolites in plants, notably characterised by their potent antioxidant properties [ 18 ].…”
Section: Introductionmentioning
confidence: 99%